Collateralised loan obligations (CLOs): A primer - Andreas A. Jobst (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
The following descriptive paper surveys the various types of loan securitisation and provides a working definition of so-called collateralised loan obligations (CLOs). Free of the common rhetoric and slogans, which sometimes substitute for understanding of the complex nature of structured finance, this paper describes the theoretical foundations of this specialised form of loan securitisation. Not only the distinctive properties of CLOs, but also the information economics inherent in the transfer of credit risk will be considered, so that we can equally privilege the critical aspects of security design in the structuring of CLO transactions.
urn:nbn:de:hebis:30-10030
Keywords: D81; G15; G21; M20; 330; Loan Securitisation; Structured Finance; CLO; ABS